Evaluation of Free-Living Nematodes Panagrellus Redivivus as Starter Food for Malaysian River Catfish, Mystus Nemurus (Cuvier and Valenciennes) Larvae - Alban Laron, Manuel (2001)
The performance of Panagrellus redivivus on growth and survival of Mystus nemurus larvae was assessed in this study. Prior to the assessment study, the optimal stocking condition for M. nemurus larvae was determined. A stocking density of 10 larvae L-1 gave the highest growth and survival during the 16-days rearing period. However a stocking range of 25-43 larvae L-1 was recommended for commercial hatchery production. The performance of P. redivivus was compared with Brachionus spp., Moina spp., Chironomus spp. and Artemia sp. Larvae fed with Chironomus spp. exhibited the best growth (P<0.05) compared to those fed with P. redivivus, Brachionus spp., Moina spp. and Artemia sp. No significant differences in growth were found among those fed with the later live foods. Nevertheless, these live foods gave a significantly higher survival than Chironomus spp. In the following study, M. nemurus larvae fed smaller P. redivivus on the first week followed by bigger Chironomus spp. showed improved survival and growth than those fed on Chironomus spp. or P. redivivus alone. This combination also gave better results than those of Artemia nauplii. Another study was conducted to determine the optimal feeding density of P. redivivus for M. nemurus larvae. The results of two feeding trials showed that the optimum feeding density on the first week and second week of feeding were 60 nematodes mL-1 and 125 nematodes mL-1, respectively. This feeding regime was adopted in the following experiment. Finally, P. redivivus was evaluated as the first food for the weaning of M. nemurus larvae to an artificial diet. The results showed no significant effect (P>0.05) of gradual weaning from Day 4 and d irect weaning at Day 8 of exogenous feeding with P. redivivus as the first food on the survival and growth of catfish larvae. P. redivivus was found to be suitable as an Artemia replacement (as the first food) for the weaning of M. nemurus larvae.